FECUNDITY AND SEX-RATIO OF TWO FRESHWATER FISHES, OMPOK BIMACULATUS AND O. MALABARICUS (BLOCH) OF THE RIVER AMARAVATHY, TAMIL NADU, INDIA - T. ARTHI; S. NAGARAJAN; K. VIJAYARAMAN; A. A. SIVAKUMAR (The Bioscan, 2013)
The fecundity estimates have been considered as important in population estimations. In the present study, fecundity was estimated in O. bimaculatus and O. malabaricus by selecting 30 ovaries for each species. In O. bimaculatus, the number of ova was found to extend from 1,831 to 19,446 in the size range of 202 to 376mm in total length and 63.8 to 328.1g in weight. In O.malabaricus, the number of ova was found to range from 2, 182 to 17, 792 in the size range171to 374mm in total length and 51.3 to 316.5g in weight. A linear relationship could be seen between (1) fecundity and total length, (2) fecundity and body weight and (3) fecundity and ovary weight in both the species. Sex-ratio in O. bimaculatus and O. malabaricus deviated from the expected 1:1 ratio during all the months of our study.